Process philosophy and political liberalism : rawls, whitehead, hartshorne - Dombrowski, Daniel A. (Edinburgh : Edinburgh University Press, 2019)
Daniel A. Dombrowski brings together the thought of the 20th-century philosophy's greatest political liberal, John Rawls, with the thought of the great process philosophers, Alfred North Whitehead and Charles Hartshorne. He shows that political liberalism is intimately linked with process philosophy, renaming it 'process liberalism'.
Introduction; 1. Reflective Equilibrium as a Process; 2. Political Liberalism and Process Thought; 3. Gamwell on 'The Comprehensive Question': A Rawlsian Critique; 4: Religion, Solitude-in-Solidarity, and the Bloodlands; 5. Heidegger, Political Philosophy, and Disequilibrium; 6. Organic Marxism and Process Liberalism; 7. From Nonhuman Animals to the Environment; Bibliography.
Includes bibliographical references (pages 195-210) and index.
JSTOR
Keywords: Rawls, John, -- 1921-2002.; Whitehead, Alfred North, -- 1861-1947.; Hartshorne, Charles, -- 1897-2000.; Hartshorne, Charles, -- 1897-2000; Rawls, John, -- 1921-2002; Whitehead, Alfred North, -- 1861-1947; Liberalism -- Philosophy; Liberalism; Process philosophy; Libéralisme -- Philosophie; Libéralisme.; Philosophie du devenir; liberalism; process philosophy; Liberalism; Liberalism -- Philosophy; Process philosophy